2017
DOI: 10.1093/dote/dow039
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal cancer's 100 most influential manuscripts: a bibliometric analysis

Abstract: Bibliometric analysis highlights key topics and publications that have shaped the understanding and management of esophageal cancer (EC). Here, the 100 most cited manuscripts in the field of EC are analyzed. The Thomson Reuters Web of Science database with the search terms 'esophageal cancer' or 'esophageal carcinoma' or 'oesophageal cancer' or 'oesophageal carcinoma' or 'gastroscopy' was used to identify all English language full manuscripts for the study. The 100 most cited papers were further analyzed by to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 92 publications
2
9
0
Order By: Relevance
“…The TC of the 100 most frequently cited papers in LC ranged from 612 to 5358. This number is considerably higher than citation classics in gastric cancer, for which the TC ranged from 299 to 2893; oesophageal cancer, for which the TC ranged from 293 to 1833; and neurosurgery or ophthalmology . The TC in different areas of expertise may vary depending on the number of researchers in a particular field.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The TC of the 100 most frequently cited papers in LC ranged from 612 to 5358. This number is considerably higher than citation classics in gastric cancer, for which the TC ranged from 299 to 2893; oesophageal cancer, for which the TC ranged from 293 to 1833; and neurosurgery or ophthalmology . The TC in different areas of expertise may vary depending on the number of researchers in a particular field.…”
Section: Discussionmentioning
confidence: 95%
“…This number is considerably higher than citation classics in gastric cancer, for which the TC ranged from 299 to 2893; oesophageal cancer, for which the TC ranged from 293 to 1833; and neurosurgery or ophthalmology. 3,7,9,16 The TC in different areas of expertise may vary depending on the number of researchers in a particular field. As the incidence of cancer continues to increase worldwide, research on various cancers is drawing increasingly more attention.…”
Section: Discussionmentioning
confidence: 99%
“…Annals of Surgery published the most articles ranked within the upper 100 ( n = 32) and has historically been the surgical journal ranked highest with an impact factor of 8.7. Journals with high-impact factors (54.42–29.35), NEJM, Lancet, JAMA, and Nature Genetics, were not represented in this analysis, yet the citations accrued by the articles identified were similar to those reported in other bibliometric analyses; colorectal cancer (7850–989) [ 109 ], gastric cancer (2893–299) [ 4 ], and oesophageal cancer (1833–293) [ 110 ]. A possible explanation relates to the novelty of the results, which may be classified relating to the scientific community in general, or confined to the field studied.…”
Section: Discussionmentioning
confidence: 99%
“…The high rate of publication within the USA has been mirrored in other studies included that looking at emergency abdominal surgery by Ellul and colleagues [7]. Other citation analyses studies by Powell et al have also shown the same pattern [110,111]. Institutions within the USA may favourably cite local research, which may explain this pattern.…”
Section: Discussionmentioning
confidence: 80%